THE PLYOMETRIC EXERCISE SINGLE LEG SPEED HOP DAN DOUBLE LEG SPEED HOP MENINGKATKAN DAYA LEDAK OTOT TUNGKAI PADA PEMAIN SEPAK BOLA PHYSIO TEAM FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - M. Widnyana; Putu Sutha Nurmawan; Ni Wayan Tianing (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2015)
Muscle power is a component of fitness that is needed by a football player. The purpose of this research was to compare the plyometric exercise single leg speed hop and double leg speed hop to increase the power of leg muscles. This research used an experimental research with Pre and Post Test Two Group Design. Samples were divided into two treatment groups, which are single leg speed hop group that consists of 12 samples and double leg speed hop group that consists of 12 samples. The exercise was carried out for four weeks with a frequency of three times in one week, from May up to June 2014 at Niti Mandala Renon field Denpasar which use standing long jump test instrument to measure the power of leg muscles. The result of this research is, Group 1 occurring on average an increase with p = 0.000 (p < 0.05), while on Group 2 occurring on average an increase with p = 0.000 (p < 0.05), once compared Group 1 and Group 2 p=0.002 (p<0.05), meaning that there was a significant increase of muscle power in each group, however Group 1 is more effective than Group 2. From this research it can be concluded that single leg speed hop is more effective to increases the power of leg muscles compared with double leg speed hop.